2016
DOI: 10.1093/aob/mcv182
|View full text |Cite
|
Sign up to set email alerts
|

Crop acquisition of phosphorus, iron and zinc from soil in cereal/legume intercropping systems: a critical review

Abstract: Background Phosphorus (P), iron (Fe) and zinc (Zn) are essential elements for plant growth and development, but their availability in soil is often limited. Intercropping contributes to increased P, Fe and Zn uptake and thereby increases yield and improves grain nutritional quality and ultimately human health. A better understanding of how intercropping leads to increased plant P, Fe and Zn availability will help to improve P-fertilizer-use efficiency and agronomic Fe and Zn biofortification.Scope This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
132
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 130 publications
4
132
0
2
Order By: Relevance
“…Similar effects of composts on plant growth have been reported by other researchers (Garcia‐Gomez et al, 2002; Perez‐Murcia et al, 2006), mainly due to the adequate nutrients, such as N, P, and K, provided by composts. Furthermore, calcium superphosphate observably increased the plant height, which could be explained by the fact that P increases the plant height of crops (Xue et al, 2016). The highest plant height including the leaves was found in PA1, which was 133 and 34% higher than that obtained in the CK and blank treatments, respectively ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Similar effects of composts on plant growth have been reported by other researchers (Garcia‐Gomez et al, 2002; Perez‐Murcia et al, 2006), mainly due to the adequate nutrients, such as N, P, and K, provided by composts. Furthermore, calcium superphosphate observably increased the plant height, which could be explained by the fact that P increases the plant height of crops (Xue et al, 2016). The highest plant height including the leaves was found in PA1, which was 133 and 34% higher than that obtained in the CK and blank treatments, respectively ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The recent review by Xue et al (2016) on crop acquisition of phosphorus, iron and zinc from soil indicated that intercropping of cereal + legume crops is the most commonly used system reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that intercropping advantages can be explained by above-ground plant–plant interaction effects on light absorption, maintenance of optimal temperatures and space, or below-ground interactions, including root–root interactions, and interactions between roots and beneficial soil microbes (Brooker et al, 2015; Li et al, 2016; Xue et al, 2016). Root–root interactions may benefit intercropped plants in several ways.…”
Section: Introductionmentioning
confidence: 99%